Kababaihan kontra Covid-19 a gender analysis of the triple roles of women members of the BHERT of Leganes, Iloilo - Helarion,Jean Rose M.
During the height of the COVID-19 pandemic, the women members of Barangay Health Emergency Response Teams in Leganes, Iloilo were the front liners in providing immediate and appropriate emergency assistance at the community level. In addition to their contribution to the COVID-19 response and community tasks, they also undertake reproductive and productive tasks in order to contribute to the improvement of the lives of not only their families, but also their communities as a whole. Primary data were gathered through in-depth, semi-structured interviews of 8 women BHERT members and KII of two LGU officials. The study utilizes Moser's Triple Roles Framework, and results of the study showed the roles and responsibilities of women BHERT members during the COVID-19 pandemic alongside their productive and reproductive roles. These roles are not mutually exclusive and can overlap, resulting in the creation of additional challenges and benefits for them. It is essential to recognize the difficulties these women have in managing their triple roles. Their full potential may be hampered by the burden of caregiving duties, gender stereotypes, and unequal access to resources and opportunities. To address the particular challenges that these women encounter, gender-responsive policies and assistance programs can be put in place, ensuring that they receive equal benefits, have access to resources, and can balance their multiple roles effectively. Thus, it is recommended that reviewing policies related to volunteer health workers is crucial so that the government and other concerned institutions can issue a policy that will promote their benefits as well.